USING TWA (THINK-WHILE-AFTER) TECHNIQUE TO IMPROVE THE ANALYTICAL EXPOSITION TEXT READING COMPREHENSION OF THE ELEVENTH GRADERS OF SMA NEGERI 2 MAGELANG IN THE SCHOOL YEAR 2018/2019 - Vidiyana Manggesti (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
Reading comprehension is a component of English skill that has to be mastered by the students. However, XI IPS 1 students of SMA Negeri 2 Magelang in the school year 2018/2019 have difficulties in comprehending reading of analytical exposition text. Thus, the writer conducted a research to overcome the problem by applying TWA technique. The objectives of this paper are to know how great is the increase of motivation in learning analytical exposition text reading comprehension of the eleventh graders of SMA Negeri 2 Magelang in the school year 2018/2019 after being taught by using TWA Technique and to know how great is the improvement of the analytical exposition text reading comprehension of the eleventh graders of SMA Negeri 2 Magelang in the school year 2018/2019 after being taught by using TWA Technique. The writer conducted a Classroom Action Research (CAR). The writer collected the data by using non-test technique (observation, questionnaire, and documentation) and test technique. Based on the result, there is increase of students’ motivation in learning reading comprehension of analytical exposition text. The results of observation, questionnaire, and documentation show that most of the students have behavioral and perception change. Moreover, the improvement also show in the test results. The writer concluded that the use of TWA technique could increase the students’ motivation in learning analytical exposition text reading comprehension and improve the students’ analytical exposition text reading comprehension.